Non-attractiveness of modern supply chains - Obeth, E.; Batt, Peter; Butler, B. (2015)
In comparison to traditional supply chains, modern supply chains potentially allow supply chain actors, including smallholder producers and traders, to improve their productivity and overall performance. While one would expect smallholder producers and traders to join modern supply chains at every opportunity, there is growing evidence to show that not all participants are willing to engage. Through open-ended interviews with banana traders, the unwillingness to participate in modern supply chains is based on perceived risk, additional workloads and a current state of comfort. Apart from that, as supermarkets still source bananas from the traditional market, there is no need for traditional retailers to switch as they can still participate in modern supply chains.